Ostracods and Biostratigraphy of Sarmord Formation (Lower Cretaceous), Surdash Anticline, Sulaimani, Kurdistan Province, North of Iraq - Omran Hawramy; Nisreen Aziz; Waleed Al- Obidee; Hazhar Ali (Iraqi Geological Journal, 2023)
A detiled systematic study of ostracods fauna in outcropped section of Sarmord Formation (Hauterivian -Barremian) in Surdash Anticline allows to detect 28 species belong to 16 genera. Among theis species Twelve were previously recorded in the sorounding area, Thirteennew species were recorded for the first time and One species renamed according to the international system of scientific nomenclature. According to the diversity and the appearance of ostracod indeviduals along the studied section, Two biozones were recognized, the first one include about 58% of the recorded ostracod specimens, while the other one includes only 42%.